1994
DOI: 10.1159/000176663
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Valvular Involvement in Systemic Lupus erythematosus and Association with Antiphospholipid Syndrome: A Matched Echocardiographic Study

Abstract: Antiphospholipid antibodies in patients with sytemic lupus erythematosus (SLE) are often associated with thrombosis, recurrent abortions and thrombocytopenia. The purpose of this study was to evaluate the prevalence of cardiac valvular abnormalities in patients with SLE and to establish the relationship between the echographic findings and the presence of an antiphospholipid syndrome. A total of 52 consecutive patients with SLE and 52 healthy sex- and age-matched controls were therefore evaluated in a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Tricuspid valve regurgitation was found in 7.6% of patients in the first three-year period as well as 3.8% in the second, third and fourth three-year periods. Metz et al [24] found aortic regurgitation in 5% of patients, tricuspid regurgitation in 5% and pulmonary regurgitation in 3%. In the present study, no pulmonary valve lesions or Libman-Sacks verrucous lesions were found.…”
Section: Discussionmentioning
confidence: 99%
“…Tricuspid valve regurgitation was found in 7.6% of patients in the first three-year period as well as 3.8% in the second, third and fourth three-year periods. Metz et al [24] found aortic regurgitation in 5% of patients, tricuspid regurgitation in 5% and pulmonary regurgitation in 3%. In the present study, no pulmonary valve lesions or Libman-Sacks verrucous lesions were found.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] Gentile et al 9 reported a relation between high aPL antibody levels and the severity of valvular lesions. We did not detect this relation.…”
Section: Discussionmentioning
confidence: 99%
“…9,13,22,23 Several articles have pointed to an association between the two, 4,5,11,19,20,24 -27 whereas others could not show the association. 5,9,13,28,29 In patients with SLE and antiphospholipid antibodies, anticardiolipin antibody binding to valvular structures has been shown. 30 However, it should be noted that vegetations are also seen on valves of patients with SLE without antiphospholipid antibodies.…”
Section: Pathogenesismentioning
confidence: 99%